(untitled) (Scientific journal of the Fergana State University, 2025)
During the years of independence in Uzbekistan, the opportunity arose to study the historical, cultural, socio-philosophical and spiritual-ethical heritage of our people. The article analyzes scientific research conducted in the first years of independence. Brief summaries of books and works of philosophers and scientists are highlighted.